PENGARUH PELATIHAN ANTAR BIDANG, SELF AFICACY, SERVANT LEDERSHIP DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA KARYAWAN PADA PT BPR BANK DAERAH KARANGANYAR - Handayani, Asih; Pratiwi, Adcharina (Surakarta Management Journal, 2024)
Banks are a form of company in the service sector. Human resources are a very valuable asset for companies in the service sector because this type of company sells services. The work performance of employees will be reflected in the service they provide to customers. The aim of this research is to determine Inter-Field Training, Self-Afficacy, Servant Leadership and Organizational Citizenship Behavior on the Performance of Employees at PT BPR Bank Daerah Karanganyar. The population of this research is employees of PT BPR Bank Daerah Karanganyar, totaling 176 people, where the sample in this research is 122 employees. Data analysis was used with the SPSS analysis tool. The results of the analysis conclude that Inter-Field Training, Self-Afficacy, Servant Leadership and Organizational Citizenship Behavior have a significant effect on employee performance.